Early Childhood Pre-Reading Literacy Skills Based On The Application Of Storytelling Methods - Rosita Dewi, Noer Azizah (Jurusan PGPAUD FIP UNNES, 2020)
Early childhood literacy is the ability to speak, read and write that children can naturally and can hone over time. Early reading literacy is a benchmark for parents in assessing children's intelligence, but early literacy skills can certainly be honed with learning activities. Storytelling is an activity to tell stories about a story that is conveyed to listeners. Storytelling has many benefits for children, and storytelling can be a fun activity for children. Children have learned many things without realizing it through storytelling.